49th IEEE Conference on Decision and Control (CDC) 2010
DOI: 10.1109/cdc.2010.5717761
|View full text |Cite
|
Sign up to set email alerts
|

Consensus for double integrator dynamics in heterogeneous networks

Abstract: In this paper we study topological properties of consensus algorithms for agents with double integrator dynamics communicating over networks modeled by undirected graphs. Unlike existing work we drop the assumption that the positions and the velocities of the agents are shared along homogeneous communication networks. In fact, our main result is that consensus can be achieved even though the networks along which position and velocity information is shared are different, and not even connected. We further provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Remark 4.5. Theorem 4.4 is closely related to recent results on partial consensus for double-integrator multi-agent systems [16,7], as will become clear from the discussion in Section 5.1.…”
Section: Stability Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…Remark 4.5. Theorem 4.4 is closely related to recent results on partial consensus for double-integrator multi-agent systems [16,7], as will become clear from the discussion in Section 5.1.…”
Section: Stability Analysismentioning
confidence: 61%
“…Hence in this case q ∈ im B T ⊂ Λ 1 . Note that the subspace im B T × Λ 0 ⊂ Λ 1 × Λ 0 is an invariant subspace with regard to the dynamics (16) or (17). We will return to this in Section 5.1.…”
Section: Mass-spring Systemsmentioning
confidence: 99%
“…It is also of great interest to quantify how much damping is needed to avoid the natural oscillation of the double integrator dynamics. In [3] it was shown that in the linear case on R N , G a only needed to have one link for the dynamics to converge to the double consensus. However, here we require G a to be connected.…”
Section: Discussionmentioning
confidence: 99%
“…In the Euclidean counterpart of this problem it is possible to guarantee convergence when only two nodes share speed information [3]. In our case, we need to assume the undirected graph G a is connected.…”
Section: B Combining Synchronization Of Coupled Oscillators With Conmentioning
confidence: 99%
“…Examples of this are the already quoted publication, the doctoral theses [14,31] and an increasing number of papers such as [1,2,15,16,18,32]. From a more mathematical perspective, some examples are [6,118,119,17,23,46] and the references within.…”
Section: Zusammenfassungmentioning
confidence: 99%